An HIV Vaccine Protective Allele in FCGR2C Associates With Increased Odds of Perinatal HIV Acquisition - Ebonwu, Joy; Lassaunière, Ria; Paximadis, Maria; Goosen, Mark; Strehlau, Renate; Gray, Glenda E.; Kuhn, Louise; Tiemessen, Caroline T. (Frontiers in Immunology, 2021)
In the Thai RV144 HIV-1 vaccine trial, a three-variant haplotype within the Fc gamma receptor 2C gene (FCGR2C) reduced the risk of HIV-1 acquisition. A follow-on trial, HVTN702, of a similar vaccine candidate found no efficacy in South Africa, where the predominant population is polymorphic for a single variant in the haplotype, c.134-96C>T (rs114945036). To investigate a role for this variant in HIV-1 acquisition in South Africans, we used the model of maternal-infant HIV-1 transmission. A nested case-control study was conducted of infants born to mothers living with HIV-1, comparing children with perinatally-acquired HIV-1 (cases, n = 176) to HIV-1-exposed uninfected children (controls, n = 349). All had received nevirapine for prevention of mother-to-child transmission. The FCGR2C copy number and expression variants (c.−386G>C, c.−120A>T c.169T>C, and c.798+1A>G) were determined using multiplex ligation-dependent probe amplification assay and the c.134-96C>T genotype with Sanger sequencing. The copy number, genotype and allele carriage were compared between groups using univariate and multivariate logistic regression. The FCGR2C c.134-96C>T genotype distribution and copy number differed significantly between HIV-1 cases and exposed-uninfected controls (P = 0.002, PBonf = 0.032 and P = 0.010, PBonf = > 0.05, respectively). The c.134-96T allele was overrepresented in the cases compared to the controls (58% vs 42%; P = 0.001, PBonf = 0.016). Adjusting for birthweight and copy number, perinatal HIV-1 acquisition was associated with c.134-96C>T (AOR = 1.89; 95% CI 1.25-2.87; P = 0.003, PBonf = 0.048) and c.169C>T (AOR = 2.39; 95% CI 1.45-3.95; P = 0.001, PBonf = 0.016) minor alleles but not the promoter variant at position c.−386G>C. The c.134-96C>T variant was in strong linkage disequilibrium with c.169C>T variant, but remained significantly associated with perinatal acquisition when adjusted for c.169C>T in multivariate analysis. In contrast to the protective effect observed in the Thai RV144 trial, we found the FCGR2C variant c.134-96T-allele associated with increased odds of perinatal HIV-1 acquisition in South African children. These findings, taken together with a similar deleterious association found with HIV-1 disease progression in South African adults, highlight the importance of elucidating the functional relevance of this variant in different populations and vaccination/disease contexts.